Addressing Discipline Disparities for Black Male Students: Linking Malleable Root Causes to Feasible and Effective Practices. Issue 2 (1st June 2018) - Cook, Clayton R.; Duong, Mylien T.; McIntosh, Kent; Fiat, Aria E.; Larson, Madeline; Pullmann, Michael D.; McGinnis, Jenna
Abstract: Longstanding discipline disparities for Black male students are associated with untoward outcomes and necessitate feasible and effective school-based solutions. This study examined the efficacy of GREET–STOP–PROMPT (GSP) as a low-cost, potentially high-yield strategy designed to intervene on putative malleable root causes proximal to teacher–student interactions. GSP relies on three core components to mitigate proximal causes of exclusionary discipline decisions, including: (a) proactive classroom management strategies; (b) a self-regulation technique to mitigate the impact of teacher biases on the response to problem behavior; and (c) reactive strategies to increase empathic, consistent, and appropriate responses to problem behavior. Overall, results from a single case experimental concurrent multiple baseline design across schools indicated that the GSP strategy yielded systematic reductions in risk ratios. More specifically, these results showed that the likelihood of Black male students receiving an office referral was cut by two thirds following implementation of the GSP strategy. In addition, findings from this study indicated that Black male students' self-reported school connections significantly improved from pre- to postintervention. Implications, limitations, and future directions of the results are discussed.